Icelandic Journalists & the Question of Professionalism - Birgir Guðmundsson; Sigurður Kristinsson (The University of Akureyri, 2015)
The question whether journalism constitutes a profession or not has been widely discussed in the literature in recent decades without a definite conclusion. Indeed some suggest that much of the contradictory views on professionalism and the professionalization of journalism may be traced to the unclear meaning of the very term “professionalism” or “professionalization” (Nolan 2008). Thus it is possible to put simultaneously forth plausible arguments suggesting de-professionalization of journalism on the one hand, and further professionalization of journalism on the other, based on different interpretations of the term “professionalism”. The terms “professional” and “professionalism” can refer to different social phenomena in different contexts. Thus an ongoing professionalization of journalism can be taking place in one sense at the same time as de-professionalization in a different sense, and of course, these different trends can also be taking place simultaneously in different parts of the media environment (Nolan, 2008; Hallin&Mancini, 2004; Witschge&Nygren, 2009; Schudson, 2001). In determining an approach to the concept of a profession it is helpful to establish some general criteria, against which journalistic practice may be measured. In finding these criteria, guidelines are given by the discussion of traditional professions - doctors, lawyers – and on that basis some characteristics can been said to signify a profession. To what extent is the work of Icelandic journalists characterised by professionalism, and to what extent do they, as an occupational group, exhibit the features normally associated with professions? The following analysis suggests that Icelandic journalists fulfil many of the key conditions associated with professions and their development in recent decades has been one of increased professionalism.